Kajian keamanan pangan dan tingkat prevalensi cemaran bakterisusu di Sentra Pengembangan Sapi Perah Cilongok - Afduha Nurus Syamsi; Triana Yuni Astuti; Hermawan Setyo Widodo (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2018)
The experiment was aimed to assess the food securitythrough physical properties, chemical composition and prevalence rate of milk bacterial contamination in Cilongok dairy cattle development center. Surveys and observations were conducted to obtain data on milking and milk processing applied by farmer and to obtain data on physical properties, chemical composition, and milk total bacterial count. The materialswere used farmer and milk samples taken 20 liters in total from 13 Andini Lestari 1 farmers and 7 Andini Lestrari 2 farmers. Data from the laboratory were analyzed descriptively based on the Standard Nasional Indonesia (SNI): 3141.1.2011, "t" test was used to distinguish milk quality based on physical properties, chemical composition and total bactery from both groups. The results showed that physical properties, chemical composition, and total bactery from both groups were not significantly different (P> 0.05). The conclusion of the research stated that Cilongok Dairy Cattle Development Center produces milk that is suitable for consumption based on physical and chemical composition in accordance with SNI standard: No.3141.1.2011 that showed low prevalence of bacterial contamination.